G561 Structured transition is associated with improved outcomes in diabetes. (May 2019) - Harmer, M; Everitt, L; Cable, L; Nagra, A; Davis, N
Abstract : Aims: To assess the impact of a structured transition tool for young people (YP) with type 1 diabetes in the transition from paediatric to adult services. Methods: In a retrospective observational study, the case notes were reviewed for young people with Type 1 diabetes that transitioned between children's and adults services at a single tertiary centre between 2011 and 2014. YP were categorised as to whether they had experienced the 'Ready Steady Go' (RSG) structured transition programme during routine clinical care (RSG versus non-RSG). Comparisons were made between the groups evaluating changes in HbA1c, cholesterol, BMI, non-elective, diabetes-related hospital admissions and documentation of advice. Results: Of 106 reviewed case notes, 71 YP underwent structured transition utilising the RSG transition programme. In evaluation pre and post-transfer of care, undergoing the RSG programme was associated with a lowering of non-elective diabetes-related hospital admissions (RSG p=0.008 versus non-RSG p=1.000) and non-HDL cholesterol (RSG p=0.049 versus non-RSG p=0.921). The widely observed rise in HbA1c post transition was not observed in YP undergoing the RSG programme (RSG p=0.629 versus non-RSG p=0.023). No differences were observed in total cholesterol or BMI. Additionally, those who underwent structured transition had higher rates of documentation surrounding key topics; including contraception and pregnancy (p=0.005). Conclusion: This study supports the role of a structured transition tool for YP with type 1 diabetes transitioning from paediatric to adult services. Improvements in markers of metabolic and diabetes control were observed in YP utilising the Ready Steady Go Programme.